Self-Perception, Empathy and Moral Self-Concept Predict Moral Concerns in Adults - Luana Vianez Moreira (Paidéia, 2018)
Moral concerns are socio-intuitive processes comprising individual and collective aspects modulated by social cognition. In this sense, the objective of this study was to investigate the relationship among self-consciousness, empathy, and individualizing (IMC) and binding moral concerns (BMC). Therefore, outlined a quantitative study in which 341 Brazilian adults (63% female) answered the instruments: Self-Reflection and Insight Scale, Empathy Scale, Moral Self-Concept Scale, and Moral Foundations Questionnaire. Data were submitted to a multiple linear regression analysis. The results indicated a positive association among IMC, moral self-concept, empathic concern and personal distress. Regarding BMC, self-reflection and perspective-taking presented negative association, as moral self-conception and empathic concern were associated positively. It is concluded that affective components of empathy and moral self-concept are good predictors of moral concerns and that high-order metacognitive processes are not predictors of IMC, but negative predictors of BMC.